Bilinear analysis of reinforced concrete structures - Liaw, Torng-Bor; Pama, Ricardo P.; The Taiwan Power Company (Bangkok : Asian Institute of Technology, 1977)
This investigation deals with the bilinear analysis of reinforced concrete structures. The true moment-curvature curve of a reinforced concrete section is derived forming the basis for the idealized bilinear moment-curvature curves which are then used in calculating the inelastic rotations at critical sections. A practical analysis which considers both elastic and inelastic flexural deformations is presented for continuous beams and frames. The theoretical results obtained are compared with previously published experimental values and the comparison was found to be very satisfactory.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1977
Keywords: Reinforced concrete